Understanding Elephant Disturbance in Human-Elephant Conflicts : Complaints and Patterns in South Peninsular Malaysia - Bakri, Nur A'alia Atierah; Mohamad Abdullah, Nazirah (Enhanced Knowledge in Sciences and Technology, 2025)
The mobility and behaviour of Asian elephants regularly cause disruptions to local residents and agriculture, making human-elephant conflicts (HEC) a major problem in South Peninsular Malaysia. With a focus on two main goals, this thesis attempts to investigate the dynamics of elephant disturbances and spot trends within these disputes. Analysing Asian elephant movement data in southern Peninsular Malaysia and comparing movements’ temporal and spatial patterns to human activity areas is the primary goal. The goal of this study is to identify patterns that lead to disturbances, including property destruction or crop raiding. In order to comprehend how elements like seasonal variations, habitat loss, and human encroachment impact the severity and distribution of conflicts over time, the second goal is to examine the relationship between the frequency and kind of disturbances and the year. This study provides important insights into the causes and trends of HEC in the area by combining movement analysis and disturbance data, and it makes suggestions for better management techniques to lessen conflicts and encourage coexistence between people and elephants.